Luto ng Diyos mga kwento ng buhay mag-asawa - Aguiling-Dalisay, Grace (Lungsod ng Quezon, Filipinas Akademya ng Sikolohiyang Pilipino Pub. House, 1995)
Relationship between couples in the Philippines.
In Tagalog.
UCWS-3208g donated by Ma. Theresa D. Ujano-Batangan - March 2018
Keywords: Marriage -- Philippines; Interpersonal relations -- Philippines; Families -- Philippines